PERSPEKTIF MAQASID AL-SYARIAH TERHADAP FENOMENA PENURUNAN MINAT MENIKAH PADA GENERASI MILENIAL DAN Z DI DESA DLAMBAH UTARA - Nikmatun Nisa; Abdullah Afif (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study examines the phenomenon of shifting attitudes toward marriage among Millennials and Generation Z in Dlambah Utara Village, Bangkalan Regency, and analyzes it using the Maqasid al-Shariah approach. This study employs a qualitative method through in-depth interviews using a case study approach. The results indicate that Millennials tend to postpone marriage due to financial burdens as part of the sandwich generation. From a Sharia perspective, this postponement constitutes a form of Hifz al-Din through the implementation of Birrul Walidain to prioritize supporting one’s parents. Among Generation Z, there is a sharp polarization of views based on gender. Generation Z men delay marriage due to economic pressure, difficulty finding employment, and anxiety regarding the tradition of living with in-laws. This is interpreted as an effort to fulfill leadership readiness (Qawwamah) and an act of prudence (ihtiyath) within Hifz al-Nasl to ensure future offspring are not neglected. Conversely, Generation Z women choose to marry immediately for economic stability and to avoid social stigmas such as the “sangkal” myth or the label of “old maid.” This decision aligns with the principle of protection (wiqayah) and the application of Sadd al-Dzari’ah to safeguard one’s honor from slander. In conclusion, this shift in marriage preferences among the rural youth is not a form of neglecting Sharia, but rather a contextual implementation of Maqasid al-Sharia amidst economic challenges and local traditions.